Hybrid Methods in Designing Sierpinski Gasket Antennas - Mudrik Alaydrus (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2010)
Sierpinki gasket antennas as example of fractal antennas show multiband characteristics. The computer simulation of Sierpinksi gasket monopole with finite ground needs prohibitively large computer memory and computational time. Hybrid methods consist of surface integral equation method and physical optics or uniform geometrical theory of diffraction is expected to alleviate this computational burdens. The full hybridization of the different methods with modifying the incoming electromagnetic waves in case of hybrid method surface integral equation method and physical optics and modification of the Greens function for hybrid method surface integral equation method and uniform geometrical theory of diffraction plays the central role in the observation. A comparison of simulation results of these different methods and are given measurements of a groups of three Sierpinksi gasket antennas are presented. The multiband characteristics of the antennas are observed with some reduction and enhancement of resonances.